Perspective of molecular immune response of SARS-COV-2 infection - Rohmah, Martina Kurnia; Rahman Nurdianto, Arif (Jurnal Teknologi Laboratorium, 2020)
COVID-19 is a type of Pneumonia caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). When COVID-19 arise in Wuhan China and rapidly spread throughout to the World, we need to learn how pathogenesis and immune responses occur in the bodies in more detail. COVID-19 is the third Severe Respiratory Disease outbreak caused by the Coronavirus in the past two decades after Severe Acute Respiratory Syndrome (SARS) in the 2002 and Middle East Respiratory Syndrome (MERS) in 2012. The Articles from PUBMED and Research Gate were searched for studies on the immune response of COVID-19 infection by SARS-CoV-2. SARS-CoV-2 increases the number of neutrophils, suppresses IFN, increases the activity of Th1/Th17, B cells, CD8+ and CD4+, and causes cytokine storms especially pro-inflammatory cytokines which can increase respiration disorders and multi-organ damage. This review tries to explain about pathogenesis and immune responses of COVID-19 to provide a reference in designing the appropriate immune intervention for treatment and therapeutic such as drug or vaccine based on the recent research progress SARS-CoV-2 and previous studies about SARS CoV and MERS CoV.